Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Setiawati, Luh Pande Eka; Putri, Yura Karlinda Wiasa (JURNAL ECONOMINA, 2024)
Company Value is a state that a business has attained as a representation of the public's confidence in the business following a number of years of operations, specifically from the time the business was founded until the present. The purpose of this study is to ascertain how the capital structure, dividend policy, company growth, managerial ownership, profitability, and capital structure affect the value of banking companies that are listed on the Indonesia Stock Exchange between 2019 and 2022. Banking companies that are listed on the Indonesia Stock Exchange between 2019 and 2022 make up the research's population. Using the purposive sampling method, the sample criteria were determined, and 32 companies were observed overall over the course of the 4-year observation period, with a sample size of 8 companies. Multiple linear regression analysis is the method used for analysis. The study's findings indicate that the value of a company is unaffected by profitability, corporate expansion, or dividend policy. The capital structure and managerial ownership both increase the value of the company.